Фаберже для русской красавицы - Жукова-Гладкова Мария (Двойной крутой детектив, 2012)
Экземпляры: ф.1 (20180511) / Инвентарный номер: 58274 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ж 86 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44